Analysis of nicotine in various organs of male mice after inhalation of cigarette smoke - Irda Fidrianny; IGNA Supradja; Andreanus A Soemardji (Indonesian Journal of Pharmacy, 2004)
Nicotine is one of dangerous components in cigarette smoke, there for concentration of nicotin in organ quantitative in organs must be determined. Qualitative and quantitative thin layer chormatographic analysis of nicotine in various organs of male mice after inhalation of cigarette smoke has been carried out. Nicotine was extracted with chloroform in ammoniacal medium and determined by spectrophotodensitometry. The nicotine content in lung is higher than kidney and liver.Key words: nicotine, lung, kidney, liver, male mice